2016
DOI: 10.1002/lt.24499
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic ex vivo liver perfusion using steen solution as perfusate for human liver transplantation: First North American results

Abstract: The European trial investigating normothermic ex vivo liver perfusion (NEVLP) as a preservation technique for liver transplantation (LT) uses gelofusine, a non-US Food and Drug Administration-approved, bovine-derived, gelatin-based perfusion solution. We report a safety and feasibility clinical NEVLP trial with human albumin-based Steen solution. Transplant outcomes of 10 human liver grafts that were perfused on the Metra device at 37 °C with Steen solution, plus 3 units of erythrocytes were compared with a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
179
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(184 citation statements)
references
References 20 publications
1
179
1
3
Order By: Relevance
“…The Group in Zurich used to monitor perfusate pO 2 , pCO 2 , and pH during perfusion under a pressure adjusted below 3 mmHg, resulting in flow rates ranging from 100 to 150 mL/min (0.13 mL/min/g liver) (69). (71). Other groups performed NMP using the Liver Assist device (Organ Assist), which is a pressure-controlled perfusion machine providing pulsatile arterial and continuous non-pulsatile portal flow via two independent rotary pump circuits perfusate generally contains 3 units of ABO compatible blood plus variable quantity of succinylated gelatin.…”
Section: Hypothermic Oxygenated Perfusion (Hope)mentioning
confidence: 99%
See 2 more Smart Citations
“…The Group in Zurich used to monitor perfusate pO 2 , pCO 2 , and pH during perfusion under a pressure adjusted below 3 mmHg, resulting in flow rates ranging from 100 to 150 mL/min (0.13 mL/min/g liver) (69). (71). Other groups performed NMP using the Liver Assist device (Organ Assist), which is a pressure-controlled perfusion machine providing pulsatile arterial and continuous non-pulsatile portal flow via two independent rotary pump circuits perfusate generally contains 3 units of ABO compatible blood plus variable quantity of succinylated gelatin.…”
Section: Hypothermic Oxygenated Perfusion (Hope)mentioning
confidence: 99%
“…Indications to ex situ NMP, results and donor and recipient characteristics are quite heterogeneous. The first experiences, were performed as attempts to resuscitate very marginal grafts already discarded by most liver transplant centers (72,78) and so far, only three randomized prospective series have been reported (48,49,71). The first human liver transplant using ex situ NMP was published by the group in Birmingham in 2016 (78).…”
Section: Normothermic Liver Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, total preservation time represents an overly cautious way to compare outcomes of cold stored versus NMP grafts, as it assumes that cumulative injury over time is similar with both modalities; this is hard for us to accept for metabolically functional livers actively producing bile ex vivo. Matching storage duration in both modalities would be difficult because livers require at least 4-6 h to stabilize during the NMP phase (3)(4)(5). Although extended NMP duration should be monitored closely in ongoing safety trials, accrued porcine and limited pilot clinical experience suggests that NMP duration is not a critical variable, especially when kept ≤24 h (4).…”
Section: To the Editormentioning
confidence: 99%
“…In contrast, normothermic ex vivo liver perfusion has recently been introduced into clinical practice investigating continuous NMP with near complete exclusion of SCS. The initial clinical studies demonstrated feasibility and safety (12,13).…”
Section: Introductionmentioning
confidence: 98%